Knowledge and Awareness about Palliative Care and Physiotherapy Management in Palliative Care among Student and Working Physiotherapists in Malaysia: A Comparative Study - Lim, Jing Yi; Heaw, Yu Chi; Ong, Jun Hui (INTI International University, 2023)
Background: Palliative care (PC) needs are increasing in Malaysia. All healthcare providers including physiotherapists have an inescapable role in increasing the quality and development of end-of-life care. The purpose of this study is to compare the level of knowledge and awareness about PC and physiotherapy management in PC between students and working physiotherapists in Malaysia. Methods: A cross-sectional study using a self-administered online questionnaire referenced to the Palliative Care Awareness Assessment Questionnaire published by Sujatha and Jayagowri (2017) was sent to final-year physiotherapy students and working physiotherapists in Malaysia. Results:107 physiotherapists and 107 students were included. Most of the participants from both groups never received training and courses about PC. Participants recognized the benefits of physiotherapy management in PC but showed inadequacy in knowledge and awareness about the skills and techniques. Overall, no significant difference (p>0.05) was shown between the groups. Conclusion: This study revealed the insufficiency of awareness and knowledge about PC from both students and working physiotherapists. It suggests that an emphasis on the development and establishment of PC in Malaysia is clearly needed especially for the working physiotherapist.